ANALISIS PENGARUH KUALITAS PRODUK, CITA RASA, DAN HARGA TERHADAP LOYALITAS PELANGGAN WAFFELIO FRANCHISE DI SURAKARTA - Justitie, Destria; Suddin, Alwi; Widajanti, Erni (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
This study discusses the significance of: (1) product quality on Waffellio Franchise customer loyalty in Surakarta, (2) taste towards Waffellio Franchise customer loyalty in Surakarta and (3) price on customer loyalty of Waffellio Franchise in Surakarta. This research is a survey method with Waffelio Franchise customers in Surakarta, with an infinite number of participants, 97 customers have been added in 17 years, and have become waffelio consumers at least ever buying a waffelio product at least 3 (three) times . Data were analyzed using instrument test, classical assumption test, and multiple linear regression analysis. The results of the study prove that: (1) Positive and significant product quality variables on customer loyalty in Waffelio Franchise in Surakarta (2) Positive and significant taste variables on customer loyalty in Waffelio Franchise in Surakarta (3) Positive and significant price variables on customer loyalty at the Waffelio Franchise in Surakarta.